PENGARUH KEDISIPLINAN GURU TERHADAP PERILAKU MENYIMPANG SISWA SDN OGOGILI, KECAMATAN DONDO, KABUPATEN TOLI TOLI, SULAWESI TENGAH (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the influence of teacher discipline on students’ deviant behavior at SDN Ogogili, Dondo District, Toli Toli Regency. The problem addressed in this research is the occurrence of student deviant behaviors such as tardiness, rule violations, and lack of engagement in learning, which are assumed to be related to the level of teacher discipline. The objective of this study is to determine whether teacher discipline significantly affects students’ deviant behavior. This research employs a quantitative approach with a causal associative design using an ex post facto method. The sample consisted of 39 students selected through proportional random sampling. Data were collected using questionnaires and observations, and analyzed using simple linear regression, t-test, and coefficient of determination (R²). The results show that teacher discipline has a significant effect on students’ deviant behavior, with a t-value of 3.824 greater than the t-table value of 1.687 and a significance level of 0.000 (<0.05). The regression equation (Y = 45.335 − 0.454X) indicates a negative relationship, meaning that higher teacher discipline leads to lower levels of deviant behavior. The coefficient of determination (R²) of 0.282 suggests that 28.2% of students’ deviant behavior is influenced by teacher discipline, while the remaining 71.8% is affected by other factors. Thus, improving teacher discipline is essential in minimizing deviant behavior and fostering a positive learning environment.